Centres and bunkers in the campaigns of the Fourth Zone of the Fifth Wilaya during the Algerian Revolution 1956-1962 - belgacem, leila (The Algerian Historical Journal, 2026)
This study deals with the most important centers and bunkers in the rural areas of the Fourth Zone of the historical fifth Wilaya between 1956 and 1962, which were prepared for the armed revolution in the eastern Province of Oran to achieve comprehensiveness and expansion. We relied on living testimonies and what we recorded from interviews at the level of the Moudjahideens Organization in Oued Rhiou and the reports of writing the history of Relizane Wilaya in 2000 and what was recorded at the level of Radio Relizane by the Moujahideens of the western Ouersenis region, as our initiative to write down the region during the armed revolution and preserve the national memory, so we tried to monitor the most important centers and bunkers in all regions and to identify their leaders and roles in the region, in order to preserve the national memory. The sacrifices made by its inhabitants were one reason for the fortification of many areas in Dahra, Ouersenis, and the outskirts of the Kalaa and Zemoura. This was one reason for the continuity and success of the revolution.